Effect of organic and nano copper at reduced dietary levels on biochemical profile and immune response of Giriraja and Swarnadhara birds - AMINULLAH, NOOR; PRABHU, T M; SURESH, B N; MALATHI, V; BAWER, MOHAMMAD DAWOOD; YATHISH, H M (The Indian Journal of Animal Sciences, 2022)
Experiments were conducted to assess the effect of dietary organic and nano-particle forms of Cu at reduced levels on serum biochemical profile and immune response in improved chickens. Giriraja chicks (n=420) were assigned to starter (1-6 weeks) and grower diets (7-10 weeks) and Swarnadhara breeders (n=224) to breeder diets (28-48 weeks) during experimentation. Control diet prepared for each phase was supplemented with inorganic CuSO4 as per ICAR recommendation and test diets with organic Cu at 100 (OC-100), 75 (OC-75) and 50% (OC-50) or with nanoparticle Cu at 75 (NC-75), 50 (NC-50) and 25% (NC-25) of control. During each phase, blood samples were collected from 8 birds in each treatment. The serum total protein and globulin was higher in OC-50 and lower in NC-50 at 3rd and 48th week. Glucose content was higher in control and OC-50 as compared to NC-50 group at 3rd week and lower in NC-75 as compared to all other groups at 10th week. Total cholesterol was lower in OC-100 and NC-75 at 10th week and in NC-75 at 48th week. Serum albumin, calcium, phosphorus, triglyceride, creatinine, SGOT and SGPT were similar among the groups during 3rd, 10th and 48th week. Antibody titre against Newcastle disease virus was higher in OC-75 and lower in NC-75 and titre against infectious Bursal disease virus was higher in OC-75 at 3rd week, while similar among the groups at 10th week. It was concluded that the dietary inclusion of organic and Nano Cu at reduced levels had no adverse effect on biochemical profile except nano Cu on immune response at 3rd week of chicken age.